Formalistic Sequences in the style of the artist Fateh Al Moudarres-geometrical tendency (Damascus University Journal for engineering sciences, 2025)
The plastic artist and painter (Mouhammad Fateh Al Moudarres 1922-1999 CE) is considered one of the most important articulations of the modernist transformation in the Syrian plastic art، He achieved a great departure from the realistic form for the sake of formalistic and stylistic modernization in the Syrian modern painting. The artistic analysis of Al-Mudarres' work since its inception reveals geometric shapes influenced by  the system of consciousness and visual vision. This tendency to geometric shapes appeared in succession in his works، evolving from subjects dealing with nature، through to social and political situations، and still life as well، So it surrounded the human world in the painting from the inside and outside، with the mediation of special techniques for the artist، Its strength was the active agent of aesthetic modernization through reduction، modification and simplification to the extent of exaggeration in the construction of the geometric-expressive form.It was necessary to reveal the sources of this geometrical tendency that penetrated the style of (Al Moudarres) and its artistic aesthetics، and at the same time it assumes a contradiction with his expressive themes!
Keywords: Formalistic Sequences; Painting- geometrical Tendency; Fateh Al Moudarres